The Effect of Investment and Labor on Economic Growth in Banten Province - Putra, Dayu; Setiawati, Ririt (Journal of Regional Economics and Development, 2026)
This research seeks to assess the effect of investment and labor on economic growth in Banten. The independent variables in this study are investment and labor, while the dependent variable is economic growth, which is proxied by Regional Gross Domestic Product data based on constant prices. The research method used is a quantitative approach with multiple linear regression analysis. The data used is secondary data obtained from the Banten Province Central Statistics Agency (BPS) for the period 2012-2023. The findings reveal that both labor and investment have a positive impact on economic growth in Banten. This can be reflected in the increase of total investment realization in Banten, which reached approximately IDR 103.85 trillion in 2023, consisting of IDR 65.88 trillion from foreign direct investment and IDR 37.97 trillion from domestic investment. Alongside the rise in investment activity, Banten’s economic growth rate reached 4.81% in 2023, supported by the expansion of employment opportunities and productive economic sectors.